KONSEP SUNNAH PERSPEKTIF MUHAMMAD SYAHRUR - Abdul Fatah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
The development of hadith’s criticism discourses has been an interesting issue in Islamic Studies. Previously, the sunnah’s concept have formulated by muhadditsin or ushuliyyīn. They have offered that to use sunna as second resource of Islamic preceptions. But, It was different one according to Muhammad Syahrur. He was launched a difference concept of sunna. As muslim scholar, he was an popular intellectual with controversial thought. This paper tries to explain about his thought on the concept of sunna. According to him, what has Muhammad said and did are said to be result of culture than revelation. He claimed that many hadiths have contradiction with al-Qur’an, may be rejected, while it is related to religious observance or moral conduct. Because, in this case Muhammad not only an prophet, but also as man as usual. The result of this article will explain that sunna not only related with one perspective of Muhammad’s prophetic, but also must be viewed with perspective that Muhammad as a man. He also rejected that sunna as second resource after al-Qur’an to decide Islamic law.